The osteopath-parent-child triad in osteopathic care in the first 2 years of life: a qualitative study - Accardi, Caterina; Cerritelli, Francesco; Bovo, Lorenza; Esteves, Jorge E. (Frontiers in Psychology, 2023)
Background: Enactivism and active inference are two important concepts in the field of osteopathy. Whilst enactivism emphasizes the role of the body and the environment in shaping our experiences and understanding of the world, active inference emphasizes the role of action and perception in shaping our experiences and understanding of the world. Together, these frameworks provide a unique perspective on the practice of osteopathy, and how it can be used to facilitate positive change in patients. Since the neonatal period is a crucial time for development, osteopaths should aim to create a therapeutic relationship. Arguably, through participatory sense-making, osteopaths can help the baby build a generative model (with positive priors) to deal with stress and needs throughout their life.Aim: Since the literature considers that interactions with the environment, which enact the patients' experiences, depending on contextual factors and communication between patient and caregiver, this research explored whether there is a correspondence between the indications in the literature and clinical practice in the management of the mother/parent-child dyad during osteopathic care on children aged 0 to 2 years old.Methods: Semi-structured interviews were conducted with a purposive sample of nine osteopaths with experience in the field of pediatrics. Interviews were transcribed verbatim, and constructivist grounded theory was used to conceptualize, collect and analyze data. Codes and categories were actively constructed through an interpretive/constructionist paradigm.The core category was the idea of the pediatric osteopath as a support for the family, not only for the child. Four additional categories were identified: (1) Preparing a safe environment for both children and parents, (2) Communication, (3) Attachment and synchrony, and (4) Synchronization.Through participatory sense-making, osteopaths manage contextual factors to establish an effective therapeutic alliance through the osteopath-parent-child triad to facilitate the construction of the child's internal generative model to promote healthy development. The therapeutic encounter is considered an encounter between embodied subjects, occurring within a field of affordances (ecological niche) that allows the interlocutors to actively participate in creating new meanings through interpersonal synchronization. Participatory sense-making and the establishment of a therapeutic alliance through the osteopath-parent-child triad are crucial to promote healthy development in the child.